MEMBANGUN HUKUM BERBASIS NILAI-NILAI INDONESIA (TINJAUAN PRISMATIKA HUKUM SEBAGAI DASAR PEMBANGUNAN HUKUM DI INDONESIA BERBASIS PANCASILA) - Purnawan D Negara (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2013)
In legal development in Indonesia there is still a lot of colonial laws that are applied, whose values a re not rooted in Indonesian society. National Legal Seminar VI in 1994 in Jakarta said that the law of a nation must be "nation-centric" which should reflect the values o f the nation. To realize that there is trouble for being too pluralistic of Indonesian society values. Prismatic concept that emphasizes the values o f balance and the values-based philosophy of the state, the fundamental norms (Staatsfundamentalnorm), and national identity that differentiates it from other nations can be used as the attempt to balance the social value of community and individualism in Indonesia's pluralistic society.